Idiopathic pulmonary fibrosis beyond the lung: understanding disease mechanisms to improve diagnosis and management - Luppi, Fabrizio; Kalluri, Meena; Faverio, Paola; Kreuter, Michael; Ferrara, Giovanni (Respiratory research, 2021)
Idiopathic pulmonary fibrosis (IPF) is a chronic and progressive disorder with an estimated median survival time of 3-5 years after diagnosis. This condition occurs primarily in elderly subjects, and epidemiological studies suggest that the main risk factors, ageing and exposure to cigarette smoke, are associated with both pulmonary and extrapulmonary comorbidities (defined as the occurrence of two or more disorders in a single individual). Ageing and senescence, through interactions with environmental factors, may contribute to the pathogenesis of IPF by various mechanisms, causing lung epithelium damage and increasing the resistance of myofibroblasts to apoptosis, eventually resulting in extracellular matrix accumulation and pulmonary fibrosis. As a paradigm, syndromes featuring short telomeres represent archetypal premature ageing syndromes and are often associated with pulmonary fibrosis. The pathophysiological features induced by ageing and senescence in patients with IPF may translate to pulmonary and extrapulmonary features, including emphysema, pulmonary hypertension, lung cancer, coronary artery disease, gastro-oesophageal reflux, diabetes mellitus and many other chronic diseases, which may lead to substantial negative consequences in terms of various outcome parameters in IPF. Therefore, the careful diagnosis and treatment of comorbidities may represent an outstanding chance to improve quality of life and survival, and it is necessary to contemplate all possible management options for IPF, including early identification and treatment of comorbidities.
Gesehen am 21.05.2021